2022
DOI: 10.1001/jamaneurol.2022.0074
|View full text |Cite
|
Sign up to set email alerts
|

Association of Intensive vs Standard Blood Pressure Control With Cerebral Blood Flow

Abstract: IMPORTANCEAntihypertensive treatments benefit cerebrovascular health and cognitive function in patients with hypertension, but it is uncertain whether an intensive blood pressure target leads to potentially harmful cerebral hypoperfusion.OBJECTIVE To investigate the association of intensive systolic blood pressure (SBP) control vs standard control with whole-brain cerebral blood flow (CBF). DESIGN, SETTING, AND PARTICIPANTSThis substudy of the Systolic Blood Pressure Intervention Trial (SPRINT) randomized clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 53 publications
2
45
0
1
Order By: Relevance
“… 8 In contrast, another recent study involving participants aged 50 years or older (mean age 67.5 years) showed that intensive anti-hypertensive treatment (to achieve systolic blood pressure target of <120 mmHg) was associated with increased, rather than decreased, perfusion in the grey and white matter. 9 Our analysis suggests that anti-hypertensive treatment has no deleterious effect on cerebral perfusion if systemic arterial blood pressure is controlled on medication and supports the conclusions of the meta-analysis conducted by Van Rijssel and colleagues. 4 These findings highlight the importance of blood pressure control not only for the purpose of reducing the risk of stroke, cardiovascular disease, heart and renal failure, but also for the benefit of maintaining adequate cerebral blood flow and protecting the brain from harmful effects of chronically reduced perfusion.…”
supporting
confidence: 87%
See 1 more Smart Citation
“… 8 In contrast, another recent study involving participants aged 50 years or older (mean age 67.5 years) showed that intensive anti-hypertensive treatment (to achieve systolic blood pressure target of <120 mmHg) was associated with increased, rather than decreased, perfusion in the grey and white matter. 9 Our analysis suggests that anti-hypertensive treatment has no deleterious effect on cerebral perfusion if systemic arterial blood pressure is controlled on medication and supports the conclusions of the meta-analysis conducted by Van Rijssel and colleagues. 4 These findings highlight the importance of blood pressure control not only for the purpose of reducing the risk of stroke, cardiovascular disease, heart and renal failure, but also for the benefit of maintaining adequate cerebral blood flow and protecting the brain from harmful effects of chronically reduced perfusion.…”
supporting
confidence: 87%
“…In a recent longitudinal study undertaken in older (mean age 77 years) individuals with hypertension, the use of anti-hypertensive medication was found to be associated with lower grey matter CBF 8 . In contrast, another recent study involving participants aged 50 years or older (mean age 67.5 years) showed that intensive anti-hypertensive treatment (to achieve systolic blood pressure target of <120 mmHg) was associated with increased, rather than decreased, perfusion in the grey and white matter 9 . Our analysis suggests that anti-hypertensive treatment has no deleterious effect on cerebral perfusion if systemic arterial blood pressure is controlled on medication and supports the conclusions of the meta-analysis conducted by Van Rijssel and colleagues 4 .…”
mentioning
confidence: 86%
“…In the currently published analysis of the SPS3 trial performed by Shihab et al [28], the authors found that even in patients with low baseline DBP and previous stroke, intensive SBP lowering did not increase the risk of stroke. The commented paper has been acknowledged in recent research showing adequate perfusion of the brain in MRI in patients with low DBP values [29]. Our findings support those of Shihab et al [28], as DBP in the chosen ML models did not improve stroke predictions.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, a meta-analysis suggested that there was no harmful effect of antihypertensive treatment on cerebral blood flow in older age ( 37 ). Secondary analysis of the SPRINT MIND randomized clinical trial study ( 38 ) showed that among 547 participants with cerebral blood flow measured at baseline, the average age was 67.5 ± 8.1 years. Compared with standard antihypertensive therapy, intensive antihypertensive therapy was related to increased not decreased cerebral perfusion, which was most obvious among participants with a history of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%